FUNCTIONAL EVALUATION: CHARACTERISTICS AND DEMAND FOR INSTITUTIONALIZED ELDERLY (Fiep Bulletin - online, 2011)
Functional capacity is one of the important markers of successful aging and quality of life of older people. The loss of this ability is associated with the prediction of fragility, dependence, institutionalization, increased risk of falls, death and mobility problems, bringing complications over time, and generating long-stay care. Given that institutionalization may result in functional decline, this study aimed to analyze the degree of independence to carry out Activities of Daily Living (ADL) of elderly residents in long-stay institutions - LPI, the city of Natal -RN. MATERIALS AND METHODS: A descriptive exploratory study conducted in charities, with a population of study consisted of a sample of 60 elderly. The study was approved by the Ethics and Research of the Federal University of Rio Grande do Norte - UFRN, in accordance with Resolution 196 / 96. Data were collected in the period between the months of August to October 2009. The instruments used were a form with demographic and socioeconomic issues and the ADL scale of Katz on the activities are fundamental to maintaining independence: the ability to feed themselves, be consistent, getting around, bathing, dressing and using the bathroom . RESULTS: We found a higher frequency of older females compared to males respectively mean age and standard deviation of 79.0 ± 16.89 years and 78.8 ± 13.15 years. The ability to perform the ADL was identified that 58.3% of the elderly were dependent for most ADL demonstrated need for assistance and the execution of daily habits. CONCLUSION: We emphasize the high rate of disability in elderly subjects, suggesting the relevance of interventions on this aspect. It is important to work in an interdisciplinary team as a central strategy in search of comprehensive health care for the elderly.
Keywords: human aging; elderly; functional capacity